1977
DOI: 10.3758/bf03209241
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive drinking during variable and random-interval food reinforcement schedules

Abstract: Rats were trained to leverpress for food and subsequently exposed to either arithmetic series or random variable-interval reinforcement schedules. Adjunctive drinking developed in all subjects exposed to arithmetic variable-interval reinforcement, but did not develop in six of the eight animals trained on the random schedule. The results suggest that adjunctive drinking is the result of an interaction between the tendency of rats to drink after eating and the ability of locally low probabilities of reinforceme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
17
2

Year Published

1979
1979
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 25 publications
4
17
2
Order By: Relevance
“…In general, the results of the present study replicate those of Lashley and Rosellini (1980) and are consistent with those of Millenson et al (1977) in demonstrating that the development of SIP is prevented or retarded when food is delivered on random schedules. More importantly, the present results show that such a schedule can support polydipsia when pellet availability is signaled by a brief stimulus that is simultaneous with pellet dispenser operation.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In general, the results of the present study replicate those of Lashley and Rosellini (1980) and are consistent with those of Millenson et al (1977) in demonstrating that the development of SIP is prevented or retarded when food is delivered on random schedules. More importantly, the present results show that such a schedule can support polydipsia when pellet availability is signaled by a brief stimulus that is simultaneous with pellet dispenser operation.…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, the Pavlovian conditioning hypothesis predicts that SIP should be difficult, if not impossible, to obtain on these schedules. In support of this prediction, Millenson et al (1977) found that six of eight animals did not develop polydipsia when food was delivered on a RI 60-sec schedule. Similarly, Lashley and Rosellini (1980) did not observe the development of polydipsia in four of six animals exposed to an unsignaled, RT l20-sec schedule.…”
supporting
confidence: 64%
See 1 more Smart Citation
“…of the water tube, drinking typically occurs in, and is restricted to, this CS -period. Different reinforcement schedules that generate different patterns of food delivery are likely to differ in the probability of occurrence and!or duration of these periods associated with no food (Lashley & Rosellini, 1980;Millenson, Allen, & Pinker, 1977). For example, under a fixed-time (FT) schedule, food is delivered to the animal with a constant interpellet interval, independently of its behavior.…”
mentioning
confidence: 99%
“…According to this view, schedule-induced drinking is minimal with short IRIs, it increases as the IRI increases, but it declines again with very long IRIs (Falk, 1966b). Similarly, adjunctive drinking is reduced when food delivery is scheduled according to a random-interval schedule, yielding food at a constant probability in time (Millenson, Allen, & Pinker, 1977; but see Plonsky, Driscoll, Warren, & Rosellini, 1984). Interestingly, inserting a minimum postreinforcement interval during which food was not available increase drinking in a random-interval schedule (Shurtleff, Delamater, & Riley, 1983).…”
mentioning
confidence: 99%